2021
DOI: 10.3390/jcm10153262
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Changes in Pulmonary Function after Valve Surgery: Oxygenation Index Early after Cardiopulmonary Is a Predictor of Postoperative Course

Abstract: Objective: To determine pulmonary functional changes that predict early clinical outcomes in valve surgery requiring long cardiopulmonary bypass (CPB). Methods: This retrospective study included 225 consecutive non-emergency valve surgeries with fast-track cardiac anesthesia between January 2014 and March 2020. Blood gas analyses before and 0, 2, 4, 8, and 14 h after CPB were investigated. Results: Median age and EuroSCORE II were 71.0 years (25–75 percentile: 59.5–77.0) and 2.46 (1.44–5.01). Patients underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Our study showed that intraoperative pleural cavity entry was a significant independent risk factor for hypoxaemia. Our results showed that hypoxaemia in paediatric cardiac surgery occurred very early [0(0-0) hours] after CPB; in most cases (83.8%), it occurred within 2 h. This phenomenon was similar to that observed in adult patients [17], e.g., PaO 2 /FiO 2 decreased significantly 2 h after CPB. Several factors may have contributed to the timing characteristics, as follows: the atelectasis produced in CPB explained most of the markedly increasing intrapulmonary shunting and hypoxaemia in the early post-CPB period (45 min after separation from CPB) [20]; the extravascular lung water increased by 52% after separation from CPB and decreased to the presurgical values 4 h postoperatively [21]; and the lung and chest wall mechanics were mainly affected from 20-30 min to 4 h after separation from CPB [22].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our study showed that intraoperative pleural cavity entry was a significant independent risk factor for hypoxaemia. Our results showed that hypoxaemia in paediatric cardiac surgery occurred very early [0(0-0) hours] after CPB; in most cases (83.8%), it occurred within 2 h. This phenomenon was similar to that observed in adult patients [17], e.g., PaO 2 /FiO 2 decreased significantly 2 h after CPB. Several factors may have contributed to the timing characteristics, as follows: the atelectasis produced in CPB explained most of the markedly increasing intrapulmonary shunting and hypoxaemia in the early post-CPB period (45 min after separation from CPB) [20]; the extravascular lung water increased by 52% after separation from CPB and decreased to the presurgical values 4 h postoperatively [21]; and the lung and chest wall mechanics were mainly affected from 20-30 min to 4 h after separation from CPB [22].…”
Section: Discussionsupporting
confidence: 85%
“…In studies involving adult patients [10,15,16], the incidence of hypoxaemia (PaO 2 / FiO 2 ≤ 200 as the marker) after CPB cardiac surgery has been reported to range from 30.6% to 54.2%. In a recent study [17], the morbidity of PaO 2 /FiO 2 < 300 measured 2 h after CPB cessation was reported to be as high as 39.1%. Herein, we used PaO 2 /FiO 2 ≤ 300 as the marker of hypoxaemia.…”
Section: Discussionmentioning
confidence: 96%
“…Compared to patients with a CPB time shorter than 75 min, the perioperative risk of death with a CPB time longer than 75 min increased sharply ( 16 ). Impaired pulmonary gas exchange is a common complication after cardiopulmonary bypass (CPB) ( 6 ). In our study, the mean CPB time in the OTE group was 112.87 ± 18.91 min, compared to 160.77 ± 52.17 min in the DE group.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria were as follows: (1) patients above 60 years of age; (2) patients presenting with isolated mitral or aortic valve lesions; (3) Eurscore ≤5 (7). The exclusion criteria were as follows: (1) patients with potential surgical complications, such as severe chest deformity and a history of right chest surgery; (2) patients with femoral arteriovenous malformations; (3) patients with severe valvular heart disease whose cardiac structure form had seriously changed with left ventricular end-diastolic diameter >60 mm or ejection fraction (EF) <50%; (4) patients in poor general condition, accompanied by multiple organ failure, such as patients with New York Heart Association (NYHA) class grade IV heart failure (7), showing no improvement after treatment; (6) patients having emergency surgery, redo-surgery; (7) moderate pulmonary hypertension (pulmonary artery systolic pressure ≥50 mmHg); (8) patients with chronic obstructive pulmonary diseases.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation